Biological evaluation of intervertebral disc cells in different formulations of gellan gum‐based hydrogels. (7th December 2012) - Khang, G; Lee, SK; Kim, HN; Silva‐Correia, J; Gomes, ME; Viegas, CAA; Dias, IR; Oliveira, JM; Reis, RL
Abstract: Gellan gum (GG)‐based hydrogels are advantageous in tissue engineering not only due to their ability to retain large quantities of water and provide a similar environment to that of natural extracellular matrix (ECM), but also because they can gelify in situ in seconds. Their mechanical properties can be fine‐tuned to mimic natural tissues such as the nucleus pulposus (NP). This study produced different formulations of GG hydrogels by mixing varying amounts of methacrylated (GG‐MA) and high‐acyl gellan gums (HA‐GG) for applications as acellular and cellular NP substitutes. The hydrogels were physicochemically characterized by dynamic mechanical analysis. Degradation and swelling abilities were assessed by soaking in a phosphate buffered saline solution for up to 170 h. Results showed that as HA‐GG content increased, the modulus of the hydrogels decreased. Moreover, increases in HA‐GG content induced greater weight loss in the GG‐MA/HA‐GG formulation compared to GG‐MA hydrogel. Potential cytotoxicity of the hydrogel was assessed by culturing rabbit NP cells up to 7 days. An MTS assay was performed by seeding rabbit NP cells onto the surface of 3D hydrogel disc formulations. Viability of rabbit NP cells encapsulated within the different hydrogel formulations was also evaluated by Calcein‐AM and ATP assays. Results showed that tunable GG‐MA/HA‐GG hydrogels were non‐cytotoxic and supported viability of rabbit NP cells. Copyright © 2012 John Wiley & Sons, Ltd.